Spectral Study of the Pollutants ( Gelbstoff) in Water Liquefaction of Some areas of Baghdad Province by Using the Technique of Raman, Flora - Ali, R . A.; AbdulMunem, O.M.; Salim, S. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research we study one of the pollutants(Gelbstoff ) such as Humic  and Fulvic Acids  in tap waters by using the technique of  Raman, Flora to some regions of Baghdad , the results appear that the tap waters  were pollutants which know yellow substance or Gelbstoff instant of suspending waters, which appear through the scattering of the incident light to same the wave length of Raman ,also calculate Raman shift which was 3640 cm-1 and force constant to band (O â€“ H ) was 743 N/m, where the peak of Raman was at the wave length 441 nm after used the excitation wave length 380 nm . The results were in an agreement with lectures [8][9][10].